Effect of Mirena intrauterine device combined with GNRH-A on endometriosis, sex hormone level and carbohydrate antigen 125: Mirena and GNRH-A effects on endometriosis - Fenghua, Yu; Rong, Shao; Juan, Song; Guan, Leilei (Cellular and Molecular Biology, 2022)
To investigate the clinical value of Mirena (levonorgestrel intrauterine sustained release system) combined with gonadotropin-releasing hormone agonist (GnRH-a) in patients with endometriosis, 80 patients with endometriosis (March 2019 ~ March 2020) were selected as the research object. According to the "random number table method", they were divided into the control group (treated with GnRH-a) and the observation group (treated with Mirena IUD combined with GnRH-a), with 40 cases included in each group. The total clinical efficacy, sex hormone level, carbohydrate antigen 125 (CA125) level, degree of pain and recurrence rate indexes were compared between the two groups. Results showed that the total effective rate of 92.50% in the observation group was higher than 75.00% in the control group (P < 0.05). Intercourse pain of dysmenorrhea and sexual intercourse pain (VAS) in the two groups were compared before treatment. After treatment, the VAS scores in the two groups decreased, and the VAS scores in the observation group were lower than those in the control group (P<0.05). The levels of E2, FSH, LH and CA125 in the observation group were lower than in the control group (P<0.05). The recurrence rate of 5.00% in the observation group was lower than 20.00% in the control group (P<0.05). In conclusion, Mirena IUD combined with GnRH-a can improve the clinical efficacy of endometriosis, improve ovarian function, effectively regulate serum factors, further alleviate the symptoms of sexual intercourse pain and dysmenorrhea, control the risk of postoperative recurrence and achieve an ideal therapeutic effect.